STRUCTURAL AND OPTICAL PROPERTIES OF NANOCRYSTALLINE Zn0.5Cd0.5S/CdS THIN FILMS FOR PHOTOVOLTAIC APPLICATIONS - JAMAL FADHIL MOHAMMAD (University of Thi-Qar Journal, 2019)
In the present work, structural and optical properties of nanocrystalline Zn0.5Cd0.5S, CdS and Zn0.5Cd0.5S / CdS thin films have been investigated in order to use as window layer for photovoltaic application. Nanocrystalline Zn0.5Cd0.5S and CdS films have been deposited on glass substrates using chemical bath deposition technique (CBD). The atomic force microscopy (AFM) images showed that the prepared nanocrystalline thin films are homogeneous and have nano size structures. XRD analysis showed that, the films have polycrystalline structure with (002) orientation. From the optical properties results, the films have high transmittance ( 70 %). The band gap is found to be higher as comparison with the bulk of the same films indicating blue shift with respect to the bulk value as a result of quantum size effect. The electrical properties results show that the resistivity of CdS, Zn0.5Cd0.5S and Zn0.5 Cd0.5S / CdS was (3.50×102, 3.43×103 and 3.18×102 ? cm ) respectively.